Determinación del concepto de mexicanismo y su identificación en los diccionarios académicos - Fernández Gordillo, Luz (El Colegio de México, 2009)
In this contribution I shall review the plural terminology that has been used by many linguists and lexicographers to precise the concept of “peculiarity or linguistic particularity of a country or a determined region, with respect to the common, general or standard language”. I shall identify the form in which academic dictionaries offer the mexicanisms and vocables which without being proper mexicanisms require references to Mexico in their corresponding definition, as well as the problems that arise for their presentation, in order to have a starting point for detailed studies on the treatment of regionalisms, both in general or integral and in differential dictionaries.